In-situ characterization of thin polymer films for applications in chemical sensing of volatile organic compounds by spectroscopic ellipsometry - Spaeth, Karin; Kraus, Gerolf; Gauglitz, Günter (Analytical and bioanalytical chemistry, 1997)
Polymer coatings are applied in many kinds of chemical sensors. The interaction with organic vapours changes the physical properties of the coating material. For optical sensors, changes in the coating volume and the complex refractive index are most important. Spectroscopic ellipsometry has been applied for the first time to the in-situ characterization of thin poly(dimethylsiloxane) films in contact with tetrachloroethene, toluene and cyclohexane vapours. The differences in bulk refractive index between organic solvent and polymer are large for toluene and tetrachloroethene and both effects were studied separately. Cyclohexane has a bulk refractive index very close to the investigated poly(dimethylsiloxane) films. Therefore the calculation of the volume fraction of the analyte in the mixture phase with the polymer is subject to large errors for vapour concentrations below 5000 ppm.